VARIATION OF THE TECHNOLOGICAL PROPERTIES OF WOOD FROM Ochroma pyramidale IN THE LONGITUDINAL AND RADIAL SENSE OF THE SLEW - Stange, Rafaela; Buss, Rodrigo; de Souza, Luana Muller; Melo, Natalia Durigon; Monteiro, Thiago Campos; Rios, Polliana D'Angelo (Floresta, 2021)
The work aimed to characterize the wood of the species Ochroma pyramidale in the longitudinal and radial direction of the tree. For the study, five six-year old trees were used. Discs were removed at different heights of the stem. The samples were obtained from each disk in different regions between the pith and bark. The preparation and the anatomical analysis of the permanent and temporary slides, chemical analyzes, and basic density measure of the stem wood were carried out according to technical standards. As a result, it was observed that the highest averages for pore diameter and fiber length were found in the region close to the bark at all heights. Regarding to the rays, it was noted that there was an interaction between the longitudinal x radial factors for most of the parameters evaluated, except for the width of the rays. For fiber lumen diameter and vessel length, the same trend line was found, the highest average observed in the region close to the pith. In the chemical analyzes, it was possible to observe that there was no significant difference in the longitudinal direction of the wood except for solubility in cold water. For basic density, there was an increase in the region closer to the pith compared to the region closer to the bark. However, in relation to the longitudinal position of the bole, the highest values were found at the base of the bole. It could be seen that the Ochroma pyramidale species has potential use for products linked to thermal and acoustic insulation, production of particleboards and pulp and paper production.